Canadian Socialism and the Woman Question, 1900-1914 - Kealey, Linda (Labour / Le Travail, 1984)
This paper examines women in the Canadian socialist movement to illuminate their role within the institutional life of the movement and to analyze the ideological dimensions of the "woman question" before 1914. Socialist adherence to the primacy of woman's role in the home and to the family wage ideal, as well as their ambivalence toward working women, and an undeveloped vision of woman's role under socialism — all served to reinforce a secondary role for women in socialist organizations. Suspicion of bourgeois women's organizations and of autonomous women's groups generally, hampered socialist women from assuming leadership roles with some notable exceptions. While socialist analysis pointed to the exploitation of women as both workers and wives and mothers, women's issues and organizations remained peripheral and subordinale to the main task of overthrowing capitalism.